Robert Haselkorn (1934–2025): Pioneer in molecular biology and microbiology - Susan S. Golden; David J. DeRosier; James E. Dahlberg; Louis A. Sherman; Bianca Brahamsha (Proceedings of the National Academy of Sciences, 2025)
Robert Haselkorn (1934–2025) began a long and impactful career during the early years of nucleic acids research when the foundations of molecular biology were being laid. Focusing first on plant viruses, and then also bacteriophage, he hit upon a cyanophage—a cyanobacterial virus—that led his group to establish cyanobacterial strains as model organisms for fundamental bacterial research. He established that the specialized cells called heterocysts that are differentiated by multicellular Anabaena ( Nostoc ) are the sites of biological nitrogen fixation, and went on to reveal mechanisms of prokaryotic development. The Haselkorn lab became a leader more broadly in prokaryotic gene, and later genome, sequencing and annotation. Appreciated for his generosity and unwavering support of his lab members, and his contributions to creating a field of cyanobacterial molecular genetics, his impact continues across molecular biology and microbiology through those whose creativity he encouraged.